2001
DOI: 10.1016/s1074-7613(01)00208-4
|View full text |Cite
|
Sign up to set email alerts
|

Gain- and Loss-of-Function Lyn Mutant Mice Define a Critical Inhibitory Role for Lyn in the Myeloid Lineage

Abstract: To investigate the role of the Lyn kinase in establishing signaling thresholds in hematopoietic cells, a gain-of-function mutation analogous to the Src Y527F-activating mutation was introduced into the Lyn gene. Intriguingly, although Lyn is widely expressed within the hematopoietic system, these mice displayed no propensity toward hematological malignancy. By contrast, analysis of aging cohorts of both loss- and gain-of-function Lyn mutant mice revealed that Lyn(-/-) mice develop splenomegaly, increased numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
215
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(240 citation statements)
references
References 53 publications
14
215
6
Order By: Relevance
“…In macrophages, loss of Lyn results in hypersensitivity to GM-CSF and M-CSF [19,34]. Previous studies have also shown that deficiency of Lyn in aged mice results in extramedullary hematopoiesis, as well as macrophage tumors in some cases [19,38]. Our studies reveal a positive role for Lyn in regulating long-term engraftment of stem cells.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…In macrophages, loss of Lyn results in hypersensitivity to GM-CSF and M-CSF [19,34]. Previous studies have also shown that deficiency of Lyn in aged mice results in extramedullary hematopoiesis, as well as macrophage tumors in some cases [19,38]. Our studies reveal a positive role for Lyn in regulating long-term engraftment of stem cells.…”
Section: Discussionsupporting
confidence: 74%
“…In both B cells as well as mast cells, loss of Lyn results in hyperactivation of AKT and the mitogen-activated protein kinase extracellular signal-regulated kinase. In macrophages, loss of Lyn results in hypersensitivity to GM-CSF and M-CSF [19,34]. Previous studies have also shown that deficiency of Lyn in aged mice results in extramedullary hematopoiesis, as well as macrophage tumors in some cases [19,38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations